Kualitas Layanan, Citra Merek Dan Pengaruhnya Terhadap Kepuasan Nasabah Dan Loyalitas Nasabah Tabungan (Studi Pada Nasabah Taplus BNI Cabang Manado) - Sondakh, Conny (Universitas Sam Ratulangi)
The purpose of this study was to analyze the influence of service quality and brand image on customer satisfaction and its impact on customer loyalty in the Customer Taplus Bank BNI Manado. Population in this study is the customer Taplus totaling 1157 people . The number of samples 270 people with accidental sampling technique . Method of data collection is done by using a questionnaire survey , and data analysis using path analysis . The results showed that the variable quality of service significantly influence customer satisfaction partially variable . Brand image variables not significant effect on customer satisfaction partially variable while customer satisfaction variables significantly influence the loyalty variable customer.Keywords : Service Quality, Brand Image, Customer Satisfaction, Customer Loyalty